Cervical myelopathy caused by soft-tissue mass in diffuse idiopathic skeletal hyperostosis - Storch, Max-Jürgen (Springer-Verlag, 2007)
A rare case of cervical spinal cord compression in diffuse idiopathic skeletal hyperostosis (DISH or Forestier’s Disease) caused by a craniocervical mass of soft-tissue is reported. The objective is to describe an uncommon mechanism of spinal cord compression in DISH. Three weeks after a cardiac infarction a 69-year-old man slowly developed spastic tetraparesis. Magnetic resonance tomography showed a craniocervical tumor compressing the spinal cord and a massive DISH of the cervical spine. An extended mass of yellowish amorphous material was removed from between the dura, the posterior odontoid process and the posterior aspect of vertebral body C2 reaching to the upper part of C3.The histologic appearance indicated connective tissue and cell-degenerated cartilaginous tissue. There was no inflammatory component and no evidence of neoplasia. No ossification of the posterior longitudinal ligament (OPLL) was found. After removal and craniocervical stabilization the patient’s neurologic function improved remarkably. The increase of mechanical stress on the atlantoaxial segment and enhanced proliferation reaction of the connective tissue in DISH are suggested as the underlying pathomechanisms in the formation of this soft-tissue mass.